Connection data rate optimisation of IEEE 802.15.3 scatternets with multirate carriers. (22nd February 2008) - Yin, Zhanping; Leung, Victor C.M.
Designed for high rate Wireless Personal Area Networks (WPANs), the IEEE 802.15.3 Medium Access Control (MAC) protocol supports peer-to-peer communications in a piconet. In this paper, we analyse the link rate distribution of an 802.15.3 piconet employing multirate carriers at the physical layer, and show that the Expected Piconet Link Rate (EPLR) decreases gradually with the piconet radius. Furthermore, the Effective Scatternet Connection Rate (ESCR) is defined to minimise the stream connection cost in a scatternet by optimising the piconet coverage. Analytical and simulation results show that direct peer-to-peer communications in 802.15.3 piconets bring a huge gain in the expected data rate of intra-piconet links. While the maximum piconet size minimises the number of piconets in the scatternet and the number of hops for a randomly chosen connection, a medium sized piconet radius optimises the scatternet connection data rate. Thus, configuration of scatternets needs to consider the piconet size and channel reuse given the number of logical channels available.